A Facile Synthesis of Quinazolin‐4(3H)‐ones via Copper‐Catalyzed One‐Pot, Three‐Component Tandem Reaction. Issue 26 (13th September 2017) - Dhiman, Shiv; Nandwana, Nitesh K.; Dhayal, Shreemala; Saini, Hitesh K.; Kumar, Dalip; Kumar, Anil
Abstract: A simple and convenient one‐pot, three‐component tandem reaction has been developed for the synthesis of substituted quinazolin‐4(3H)‐ones using CuI/L‐proline as catalytic system. A series of 35 quinazolin‐4(3H)‐ones was synthesized in good to high yield. The method involves copper‐catalyzed double C−N coupling, reductive amination, condensation, cyclization and aerobic oxidation. Good functional group tolerance, mild reaction condition, readily available starting materials and user friendly procedure makes this protocol practically good and attractive method for the synthesis of quinazolin‐4(3H)‐ones. Abstract : A simple and convenient one‐pot three‐component method for the synthesis of substituted quinazolin‐4(3H)‐ones in moderate to good yield from 2‐bromobenzamides, aldehydes and sodium azide using CuI/L‐proline as catalytic system. The method was applicable for the gram scale synthesis of quinazolin‐4(3H)‐ones.